Cadmium exposure activates NADPH oxidase, renin–angiotensin system and cyclooxygenase 2 pathways in arteries, inducing hypertension and vascular damage. (15th October 2020) - Pinheiro Júnior, José Eudes Gomes; Moraes, Paola Zambelli; Rodriguez, Marina Diaz; Simões, Maylla Ronacher; Cibin, Francielli; Pinton, Simone; Barbosa Junior, Fernando; Peçanha, Franck Maciel; Vassallo, Dalton Valentim; Miguel, Marta; Wiggers, Giulia Alessandra
Graphical abstract: Highlights: Exposure to 1 mg/kg of Cd for 14 days induced hypertension Exposure to 1 mg/kg of Cd for 14 days induced vascular dysfunction in MRA and aorta. All vascular changes were accompanied by an increased ROS production Cd exposure activates NADPH oxidase, RAS and COX-2 pathway Abstract: Exposure to high concentrations of cadmium (Cd), widely used in many industries and found in air, food and contaminated water, is not uncommon. Cd damages the cardiovascular system, but the vascular mechanisms involved are not fully understood. This study investigated the mechanisms involved in cardiovascular damage after exposure to high Cd concentrations. Three-month-old male Wistar rats were treated intraperitoneally for 14 days with distilled water (Untreated group) or 1 mg/kg cadmium chloride (Cd group). We investigated the systolic blood pressure (SBP) and vascular reactivity of mesenteric resistance arteries (MRA) and the aorta by analysing contractile and relaxation responses in the absence and presence of the endothelium; we also evaluated pathways involved in vascular tone regulation. Superoxide anion production, COX-2 protein expression and in situ detection of COX-2, AT-1, and NOX-1 were evaluated. Oxidative status, creatinine level and angiotensin-converting enzyme (ACE) activity in plasma were also evaluated. Fourteen-day exposure to a high Cd concentration induced hypertension associated with vascular dysfunction in MRA and the aorta. In both vessels, there was increased participation of cyclooxygenase 2 (COX2), angiotensin II type 1 (AT1) receptor and NOX1. MRA also presented endothelial dysfunction, denoted by impaired acetylcholine-mediated relaxation. All vascular changes were accompanied by increased reactive oxygen species production and COX2, NOX1 and AT1 receptor expression in vascular tissue. Overall, high Cd concentrations induced cardiovascular damage: hypertension, endothelial dysfunction and vascular damage in conductance and resistance arteries, NADPH oxidase, renin–angiotensin system and COX2 pathway activation.